Integrating desmos and songket motifs: A PMRI-based learning trajectory for rotation - Puja Teressa Fawensi; Zulkardi Zulkardi; Ely Susanti; Meryansumayeka Meryansumayeka (Universitas Hamzanwadi, 2026)
This study is motivated by students’ low conceptual understanding and spatial reasoning in rotation, as well as the limited integration of local cultural contexts with digital technology in mathematics learning. It aims to design and validate a PMRI-based Hypothetical Learning Trajectory (HLT) integrating Songket Mak Raje and Desmos to develop students’ conceptual understanding and spatial reasoning on rotation. The study employs a design research method of the validation study type, involving 6 students in the pilot experiment and 36 students in the teaching experiment. The main instrument is a Desmos-based E-LAS. Data were collected through observation, interviews, and analysis of students’ work documents and analyzed qualitatively using thematic and retrospective approaches. The results show that the developed HLT is valid and effective in developing students’ conceptual understanding and spatial reasoning. Retrospective analysis produced a Local Instructional Theory (LIT) as a refinement of the HLT, emphasizing gradual scaffolding, explicit articulation of rotation properties through guided inquiry before formal generalization, and early introduction of non-contextual problems with geometric constraints to foster spatial reasoning. This study implies a model for integrating ethnomathematics and digital technology, a PMRI-based LIT as a guide for instructional design, and a practical and validated Desmos-based E-LAS prototype.